1985
DOI: 10.1080/00288233.1985.10430435
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation in sainfoin (Onobrychis viciifolia) 1. Responses to changes in nitrogen nutrition

Abstract: Development and nodulation of the forage legume sainfoin (Onobrychis viciifolia Scop.) were observed under glasshouse conditions for 50 days after sowing. Growth changes caused by different nitrogen (N) nutrition were investigated from Day 50. The quantity of nodule tissue produced compared favourably with values reported for a range oflegumes. In spite of this, the symbiotic N 2fixing system of sainfoin appeared unable to provide sufficient N to meet the plant's requirements. The relative growth rate of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Due to the symbiosis with N 2 ‐fixing rhizobia, perennial forage legumes have the opportunity to reduce N requirements, thereby potentially enhancing the sustainability of forage‐based livestock production systems (Carlsson & Huss‐Danell, ). However, Hume and Withers () and Hume, Withers, and Rhoades () provided a negative perspective on N 2 fixation in sainfoin: There was not enough N fixation to fully support the plant, resulting in larger root systems and lower shoot growth rate compared to plants supplied with mineral N. However, fertilization with N supplanted N 2 fixation before it augmented N supply to the plant when using a commercial rhizobium culture. Large pink nodules were formed suggesting that the inoculant was effective (Hume & Withers, ; Hume et al., ).…”
Section: Environmental Impacts Of Sainfoin In Livestock Systemsmentioning
confidence: 99%
“…Due to the symbiosis with N 2 ‐fixing rhizobia, perennial forage legumes have the opportunity to reduce N requirements, thereby potentially enhancing the sustainability of forage‐based livestock production systems (Carlsson & Huss‐Danell, ). However, Hume and Withers () and Hume, Withers, and Rhoades () provided a negative perspective on N 2 fixation in sainfoin: There was not enough N fixation to fully support the plant, resulting in larger root systems and lower shoot growth rate compared to plants supplied with mineral N. However, fertilization with N supplanted N 2 fixation before it augmented N supply to the plant when using a commercial rhizobium culture. Large pink nodules were formed suggesting that the inoculant was effective (Hume & Withers, ; Hume et al., ).…”
Section: Environmental Impacts Of Sainfoin In Livestock Systemsmentioning
confidence: 99%
“…Only chicory was considered further for the quantification of aerial fixed N. The N dfa achieved by sainfoin, based on chicory as a reference species, ranged from 82.8 to 86.7% and was in agreement with that of other forage legumes such as alfalfa and white clover . In spite of the plentiful available data regarding the effects of different strain inoculations in sainfoin and its N fixation under glasshouse conditions estimated by acetylene reduction assays, very little information an N dfa values of sainfoin obtained in the field by isotopic methods is available . Provorov and Tikhonovich reported an N dfa value of 80% determined using the isotope dilution method under Russian conditions.…”
Section: Resultsmentioning
confidence: 99%
“…31 In spite of the plentiful available data regarding the effects of different strain inoculations in sainfoin and its N fixation under glasshouse conditions estimated by acetylene reduction assays, very little information an N dfa values of sainfoin obtained in the field by isotopic methods is available. 13,14,[32][33][34] reported an N dfa value of 80% determined using the isotope dilution method under Russian conditions. In a biodiversity experiment in Germany, Roscher et al 35 reported N dfa values ranging from about 65 to 75% obtained using the natural abundance method.…”
Section: Nitrogen Fixationmentioning
confidence: 99%
“…In contrast to the meagre data on P and K response, mention is often made in the literature to the fact that sainfoin responds readily to N fertilizer (Jensen & Sharp, 1968;Meyer, 1975) because of its inefficient N2 fixing ability (Hume & Withers, 1985).…”
Section: 'Ntroductionmentioning
confidence: 97%
“…This finding corresponds with some published data (Ditterline & Cooper, 1975;Wilman & Asiedu, 1983;McGraw & Marten, 1986). The relatively low CP content obtained in sainfoin can probably be related to inefficient N2 fixation of this species (Hume & Withers, 1985).…”
Section: Field Trialmentioning
confidence: 99%